Properties of Annealed Atomic-Layer-Deposited Ruthenium from Ru(DMBD)(CO)3 and Oxygen. (19th June 2018) - Hayes, Michael Howard; Dezelah, Charles L.; Conley, John F.
Abstract : The effective work function, resistivity and morphology of ruthenium deposited by thermal atomic layer deposition using Ru(DMBD)(CO)3 and oxygen are investigated. The resistivity and surface roughness are examined before and after annealing in an N2 ambient at up to 500 °C. The average as-deposited resistivity of 16.1 μΩ-cm is reduced to an average of 13.7 μΩ-cm after 20 minutes of annealing. Subsequent annealing has no significant impact. GIXRD shows a polycrystalline hexagonal Ru thin film with a slight (001) growth preference as-deposited. AFM pre- and post-anneal revealed the growth of crystallites through a slight roughening of the surface. The effective work function of as-deposited Ru on ALD Al2 O3 was determined to be 5.3 eV.